Strategi Penumbuhan Nilai-nilai Pendidikan Islam Bagi Remaja: Studi di Majelis Taklim Nurul Amin Denasri Kulon Batang - Qonita, Rifatul; Prayogi, Arditya (Bustanul Ulum Journal of Islamic Education, 2023)
This article was written against the background of the important role of the taklim assembly in fostering the value of Islamic education in society, especially among teenagers. In this case, the taklim assembly can play a role in providing Islamic education for teenagers. This article aims to provide an overview of the taklim council's strategy in fostering the value of Islamic education for village youth, as well as what are the supporting and inhibiting factors in fostering the value of Islamic education for village youth. This article was written using a qualitative approach with a type of field research. The data sources in this research consisted of two taklim council teachers and two students (teenagers). Data collection techniques used were interviews, observation and documentation. The data obtained was then analyzed using the stages of data condensation, data presentation, and drawing conclusions. From the results of the study, it is clear that the values of Islamic education taught by the taklim assembly here are moral values, worship values, and creed values. In implementing the values of Islamic education, the taklim assembly applies strategies in the form of integration with subjects, self-development, refraction, modeling, counseling, and becoming a competent caregiver. Things that are supporting factors in implementing Islamic education, namely the existence of family support, a supportive environment, enthusiasm from teenagers, the availability of adequate facilities and infrastructure. Meanwhile, the inhibiting factor is the lack of discipline in students, the emergence of a feeling of laziness.